Pemberdayaan Ibu Rumah Tangga Terhadap Pengelolaan Pangan Lokal Berbasis Kelor Dalam Mencegah Stunting Di Desa Oefeto - Marthina Raga Lay; Theny I.B. Kurniati Pah; Jacob Wadu; Adriana Fallo (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Stunting is a condition of failure to thrive in children under five (infants under 5 years of age as a result of chronic malnutrition, so children are too short for their age. Stunting is not only caused by factors of malnutrition experienced by pregnant women and children under five, but there are many factors that causes it, and one of the factors is the lack of family access to nutritious food because people's purchasing power is low. Adequate nutritional intake is a prerequisite for achieving good nutritional status. Moringa is a multipurpose vegetable crop. Almost all parts of this moringa plant can be used as a food source because it contains active compounds and complete nutrition. Family independence is important in preventing nutrition and health problems. This service aims to increase the knowledge and skills of housewives in local moringa-based food processing and provide an understanding of the risks of stunting in children and how to prevent it by using the lecture / counseling method and processing practices.